Influence of Intensity of Smartphone Use with Physical Fitness of Students during the Covid-19 Pandemic - Ujang Nurdin; Sigit Nugroho; Betrix Teofa Perkasa Wibafied Billy Yachsie; Amri Hartanto; Andrian Rahman Ayudi (Budapest International Research and Critics University, 2022)
This study aims to determine the relationship between the intensity of smartphone use and physical fitness. This type of research is descriptive quantitative, with an ex post facto approach. The population in this study were students of class VIII SMP Negeri 4 Purwokerto, Banyumas Regency, totaling 212 students. Determination of the sample size in this study using the Slovin formula with a sampling error of 10% totaling 68 students. Instruments to measure physical fitness are TKJI tests aged 13-15 years and the intensity of smartphone use is measured using a questionnaire. The data analysis technique used SPSS 2020. The results showed that there was a significant relationship between the intensity of smartphone use and physical fitness, with a calculated r value of -0.619.